Guiding The Legality of UMKM Sticky Tape of Desa Picungpugur - Suzana, Anna; Nuryanto, Muchamad Andi; Fitriyani, Chiandria; Habibah, Nopi; Sofyan, Devi Nurfransisca; Agus Kurnia Nugraha, Agus Kurnia (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2024)
Picungpugur village is one of the areas in Lemahabang District that has characteristic local products of sticky tape wrapped from guava leaves. Most of the population works as business owners so it requires understanding and knowledge and skills about entrepreneurship especially on the legality of the business. Our program aims to help the development of MSMEs in Lemahabang Especially in Picungpugur Village, Cirebon Regency. In the presence of the Establishment of legality the parent number sought (NIB) is essential to increase the competitiveness of the business while providing formal legitimacy. The service aims to raise awareness about the importance of business legality for SMEs in order to compete in the open market. In-depth interviews, observations, and documentation were used for the implementation. As a result of the implementation, an Endeavor Parent Number (NIB) is issued, which serves as a legal umbrella for undertakings that are authorized and recognized by the state through the OSS Institution (also known as Online Single Submission). Through this study, it is expected that Business Participants will know how or strategies applied to be able to help the development of MSMEs to be more creative and innovative that exist in Picungpugur village